PELATIHAN MANAJEMEN PENDIDIKAN BERBASIS BUDAYA DI MOJOKERTO - Amrozi Khamidi; Erny Roesminingsih; Karwanto Karwanto; Muhammad Sholeh; Sri Setyowati (Program Studi S1, S2, S3 Mananajemen Pendidikan Universitas Negeri Surabaya, 2022)
Mojokerto as a heritage area of ​​the Majapahit kingdom has a diverse cultural heritage. Various Majapahit relics can be seen with the existence of Majapahit heritage temples in Mojokerto, there are Brahu Temples, Bajang Ratu, Rat Temples, Dentong Temples, Segaran Ponds. There is also a trowulan museum. In the field of arts and culture there are dance and music arts as well as crafts such as sculpting and metal crafts. In order to preserve all these cultures, it is considered necessary to include culture in the school curriculum both in subjects (local content) and extracurricular such as arts and culture and the existence of outing classes or learning outside the classroom to get to know the original culture of Mojokerto, the legacy of the Majapahit kingdom. PKM with the theme of Culture-Based Education Management Training in Mojokerto is expected to be able to contribute to the city of Mojokerto in terms of developing culture-based education. In this case, PKM activities are centered in Ir. Soekarno is small and the Wayang Museum which is part of the history and culture developed by the Mojokerto city government as a Center for Education and History Tourism. The output of this PKM activity in addition to the Workshop in Mojokerto, the results of this PKM will also be recorded as an ISBN book and scientific articles will be compiled to be published in the National PKM Journal. The technology transfer provided in this PKM is the development of the school curriculum in Mojokerto City by adopting a Culture-based curriculum. In its implementation, PKM from UNESA MP Masters invited art and culture teachers and elementary school crafts in Mojokerto City to provide strengthening of Culture-Based Education Management. In the future, this PKM can realize SD Purwotengah as a Cultural Heritage and Educational Tourism in Mojokerto City.